Isolation and culture of green algae Haematococcus pluvialis and its molecular diversity - Noroozi, Mostafa (2011)
Haematococcus pluvialis (Flotow) is a unicellular green alga from volvocale algae living in temporary shallow freshwater ponds and has many applications for humans, poultry and fishery due to its ability to produce astaxanthin. The main objective of this study was isolation of new strains from the water bodies in Iran and to evaluate the growth of nine strains of H. pluvialis obtained from four countries (four strains from Iran, two strains from Finland, one strain from Switzerland and three strains from USA), in distinct growth media and also determine their genetic diversity based on ISSR and RAPD. The traditional methods and our new found method were used to isolate the four Iranian species. In the new method the algal suspension were exposed to high light intensity to make the cells transform to big, red cyst form which is easy to see and easier to separate from other organisms. The isolated algae were cultured in Bold medium as general algal medium to obtain enough biomass to inoculums to other media. All the cultures were done under sterile condition using pre-autoclaved chemicals and microbiological filter passed air for aeration. Two methods were used to detect the biomass of cultivated cells including 0.8 micron Milipore filter paper and DMSO method to extract and measure chlorophyll concentration in all media and strains. The astaxanthin concentration was measured by spectrophotometer and HPLC methods which DMSO was used to extract pigment from the cyst of H. pluvialis. In this research, the cultured media were centrifuged to precipitate the biomass and DNA was extracted from 10 different strains of H. pluvialis using the Dellaporta method with the liquid nitrogen and mortar. Genetic similarity study was carried out using 14 ISSR and 12 RAPD primers. The biomass obtained from Bold culture were used for the purpose of inoculation to four other media namely: NIES, OHM, Mixotroph and COMBO (the COMBO medium was used for the first time to culture H. pluvialis). The results of this study depicted that Mixotroph growth medium gave the best biomass of 0.577 g dry wt/l followed by COMBO and OHM media respectively. Moreover, the strains showed geographical differentiations as a result the Iran4 and USA2 strains produced highest biomass and the Finland2 showed the slowest growth. Molecular markers are suitable tools for the purpose of finding out genetic variations in organisms; however there is no study conducted on ISSR or RAPD molecular markers regarding this organism. The molecular weights of the bands produced ranged from 3.4 to 0.14 Kb. The PCA and dendrogram clustered the H. pluvialis strains into various groups according to their geographical origins. The lowest genetic similarity was between the Iran2 and USA1 strains and the highest genetic similarity was between Finland1 and Finland2. The results showed that ISSR and RAPD markers are useful for the genetic diversity studies of Haematococcus as they showed clustering of strains from similar geographical origins. As a conclusion different strains of H. pluvialis shows various abilities in physiological, metabolites and biochemical traits. The various characteristics of strains explain the necessity of survey on new resources to discover more efficient strains.